1991
DOI: 10.1007/bf00250339
|View full text |Cite
|
Sign up to set email alerts
|

Unterschiedliche Wirksamkeit von zwei Pr�paraten mit niedermolekularem Heparin bei Patienten mit elektivem H�ftgelenksersatz

Abstract: In an open randomised trial 3 regimen of prophylaxis for deep vein thrombosis were compared in 105 patients undergoing elective hip arthroplasty. One part of the patients received one injection daily of a low molecular weight heparin, another part was treated with one injection of a combination containing a different type of low molecular weight heparin + dihydroergotamine per day and a third part of the patients received 3 applications of 5000 IU unfractionated heparin per day. The frequency of DVT determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
1

Year Published

1992
1992
1998
1998

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 7 publications
0
1
1
Order By: Relevance
“…cemented arthroplasty had DVT, as compared to 15.5% with notcemented arthroplasty, was not expected. This is in contrast to the results of a clinical study conducted by Weber et al who found a higher incidence of DVT in patients with cemented than in those with notcemented arthroplasty (15). However, the findings of Weber et al might be due to the fact that there was a difference in the age of about 2 0 years between the two study populations in question.…”
contrasting
confidence: 60%
“…cemented arthroplasty had DVT, as compared to 15.5% with notcemented arthroplasty, was not expected. This is in contrast to the results of a clinical study conducted by Weber et al who found a higher incidence of DVT in patients with cemented than in those with notcemented arthroplasty (15). However, the findings of Weber et al might be due to the fact that there was a difference in the age of about 2 0 years between the two study populations in question.…”
contrasting
confidence: 60%
“…Recent studies have shown that different LMWHs require different dose regimens and that their antithrombotic effect is different (14). The cause of this must be seen in their different molecular weight distribution, sulphation degree, charge density and bioavailability (15,16).…”
Section: Discussionmentioning
confidence: 99%